Functionalized Dialdehydes as Promising Scaffolds for Access to Heterocycles and β-Amino Acids: Synthesis of Fluorinated Piperidine and Azepane Derivatives - Ábrahámi, Renáta A.; Kiss, Loránd; Fustero, Santos; Fülöp, Ferenc (Synthesis, 2017)
Functionalized dialdehydes are considered important substrates that can be transformed into various substituted heterocyclic, alicyclic, and polysubstituted compounds. Here, we report a robust stereocontrolled procedure for the synthesis of novel functionalized trifluoromethyl-containing piperidine and azepane derivatives, based on oxidative ring cleavage of the C=C bond of diversely substituted cycloalkenes, followed by reductive ring closure of the diformyl intermediates in the presence of fluorine-containing amines.
Keywords: aldehydes; alkylation; amino acids; bioorganic chemistry; heterocycles; piperidines; expansion